Kanoma: Learning Media to Improve Students’ Understanding Mathematical Concepts - Sigarini, Khofifah Aluh; Fitriana, Laila; Setiawan, Rubono (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
This research was conducted to determine the validity, practicality, and effectiveness of Kanoma’s learning media in improving the understanding of mathematical concepts in high school students in class X. This research applied development research design with the PLOMP approach developed by Tjeerd Plomp. The stages of development using the PLOMP approach include preliminary investigation, product design, construction, testing, and implementation. The population in this research were all ten-grade students at a vocational high school. The research sample consisted of 16 students in the experimental class and 14 students in the control class. These students were selected randomly using the cluster random sampling technique. The instruments utilized in the study included assessments by media experts, questionnaires for students and teachers, and pretest and posttest evaluations of mathematical understanding. The instruments given to media experts is used to validate the Kanoma media and its content. The questionnaires for students and teachers were used to test the practicality of the developed Kanoma media. These quistionnaires gathered feedback on how easy and useful the media was in a classroom setting. The pretest and posttest were designed to measure students’ understanding of mathematical concepts related to finding the roots of quadratic equations. The average value given by material experts from the two validators of Kanoma’s media is 0.82. The average value given by media experts from the two validators is 0.90. The results show that the Kanoma media was categorized as “very valid” by both material and media experts. This indicates that media was suitable for use by class X students in senior high school. Kanoma media is also classified as practical based on the average percentage of student and teacher responses. The responses from students scored 73%, categorized as “practice”. The responses from teachers scored 81%, categorized as “very practice.” Kanoma media is effective based on the Mann-Whitney Asyptotic Sig. (0.002) <α (0.05). The results showed a significant improvement in mathematical understanding. Students who used the Kanoma media had a better grasp of the mathematical concepts than those who did not.